The crystal structure of [(1,10-phenantroline-κ2N,N′)-bis(6-phenylpyridine-2-carboxylato-κ2N,O)manganese(II)] monohydrate, C36H26N4O5Mn - Hua-Xiang Zhang; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures)
C36H26N4O5Mn, orthorhombic, P212121 (no. 19), a = 10.7134(7) Å, b = 10.7573(10) Å, c = 26.6304(18) Å, β = 90°, V = 3069.1(4) Å3, Z = 4, Rgt(F) = 0.0454, wRref(F2) = 0.0890, T = 220 K.